A novel ex-ante tariff scheme for cost recovery of transmission investments under elasticity of demand - De Paola, A; Savelli, I; Morstyn, T (Institute of Electrical and Electronics Engineers, 2020)
This paper proposes the application of ex-ante dynamic network tariffs for the recovery of investment costs in transmission network planning. The tariffs design is integrated in the long-term network expansion problem and in the underlying market clearing process, accounting for the impact of tariffs on the bidding strategies of price-responsive participants. Differently from the established ex-post approach, this method avoids negative surplus for marginal users and untruthful biddings. The methodology is described analytically and applied to a relevant case study, which demonstrates the positive effect of ex-ante tariffs in terms of increased social welfare, emphasizing their positive impact in scenarios with high price-elasticity of demand.